2011
DOI: 10.1177/0963662510392484
|View full text |Cite
|
Sign up to set email alerts
|

Representations of swine flu: perspectives from a Malaysian pig farm

Abstract: Novel influenza viruses are seen, internationally, as posing considerable health challenges, but public responses to such viruses are often rooted in cultural representations of disease and risk. However, little research has been conducted in locations associated with the origin of a pandemic. We examined representations and risk perceptions associated with swine flu amongst 120 Malaysian pig farmers. Thirty-seven percent of respondents felt at particular risk of infection, two-thirds were somewhat or very con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
(65 reference statements)
1
13
0
1
Order By: Relevance
“…Producers believed that most H1N1/09 was transmitted through direct or close contact with a sick person. Similar perceptions were reported among pig producers in Malaysia, who believed that avoiding crowds and contact with infected people were effective ways of protection against H1N1/09 infection (Goodwin et al, 2011). Perceptions on transmission pathways among pig producers were also similar to those reported by the general public in the Greater Sydney area (Dhand et al, 2011).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Producers believed that most H1N1/09 was transmitted through direct or close contact with a sick person. Similar perceptions were reported among pig producers in Malaysia, who believed that avoiding crowds and contact with infected people were effective ways of protection against H1N1/09 infection (Goodwin et al, 2011). Perceptions on transmission pathways among pig producers were also similar to those reported by the general public in the Greater Sydney area (Dhand et al, 2011).…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have investigated public perceptions about the Influenza Pandemic H1N1/09 (Goodwin et al, 2009;Lau et al, 2009;Dhand et al, 2011;Lau et al, 2011); however, limited information is available on pig producers' perceptions and experiences (Goodwin et al, 2011). This cross-sectional observational study was conducted at the height of the outbreak in the human population in Australia and before the virus was reported for the first time in an Australian piggery in July 2009 (OIE, 2009b;Holyoake et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also possible that the high seroprevalence of SPU was caused by its geographical area as it is mostly covered with agriculture land and also located at the border of Kedah DarulAman and Thailand which are areas known to be endemic for the disease. At the same time, we believed that the reallocation of time and resources by the authorities to control other pandemics and re-emerging infections, notably the multiple outbreaks of FMD (Edwards, 2004;Wongsathapornchai et al, 2008), bird flu (H5N1) (Morris et al, 2005) and swine flu (H1N1) (Goodwin et al, 2011) led to asubstantial reduction in of nationwide brucellosis surveillance and control program. Previous studies have also reported that location, region or area have a significant correlation with brucellosis seropositivity, which, according to the authors, is attributable to management practices and other agroecological factors (Megersa et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In other societies, the social representations of the H1N1 virus were markedly different. In Malaysia, pig farmers often reported that friends had avoided them because of the epidemic as well as suggesting that certain groups such as homosexuals, the homeless and prostitutes were more likely to contract the virus [14]. And while the media are attributed responsibility for generating social representations of pandemics [21], the role of social media must be accorded increasing importance in light of its increased use.…”
Section: Social Psychology and Extensive Influencementioning
confidence: 99%